2022
DOI: 10.2196/38952
|View full text |Cite
|
Sign up to set email alerts
|

Instructor Development Workshops for Advanced Life Support Training Courses Held in a Fully Virtual Space: Observational Study

Abstract: Background Various face-to-face training opportunities have been lost due to the COVID-19 pandemic. Instructor development workshops for advanced resuscitation (ie, advanced life support) training courses are no exception. Virtual reality (VR) is an attractive strategy for remote training. However, to our knowledge, there are no reports of resuscitation instructor training programs being held in a virtual space. Objective This study aimed to investigate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In particular, VR offers a captivating way to learn in the classroom and beyond. CPR training in virtual worlds has been proposed for a decade;[ 80 ] recent research has found that this type of simulation generates a stronger sense of empathy in users than regular video because of an effect known as embodied cognition. [ 81 ] The VR methodology for CPR training positively impacts procedural knowledge, manual skills, and self-efficacy, with and without the physical mannequin.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, VR offers a captivating way to learn in the classroom and beyond. CPR training in virtual worlds has been proposed for a decade;[ 80 ] recent research has found that this type of simulation generates a stronger sense of empathy in users than regular video because of an effect known as embodied cognition. [ 81 ] The VR methodology for CPR training positively impacts procedural knowledge, manual skills, and self-efficacy, with and without the physical mannequin.…”
Section: Introductionmentioning
confidence: 99%